EVALUATION OF THE IMPLEMENTATION OF A NUTRITION SELF-SUFFICIENCY POLICY TO OVERCOME STUNTING - Sudarmi, Sudarmi (Universitas Aisyah Pringsewu, 2024)
ABSTRACTThe strategy to accelerate the stunting reduction target of the South Lampung District Government of Lampung Province launched a nutrition self-sufficiency policy movement. The results of this evaluation are expected to provide an overview and provide input and recommendations for policymakers on accelerating the reduction and suppression of stunting cases as well as policy development in the future. Type of evaluation research with the evaluation model used by CIPP, which aims to evaluate the context, inputs, processes, and products of nutrition self-sufficiency policy. Data collection techniques using in-depth interviews, FGDs, documentation studies using research protocols, and CIPP model variables have become interview guide tools. The types of data collected are primary data to assess the implementation of the nutrition self-sufficiency policy and secondary data. Data analysis includes data validation, classifying data according to focus and research questions, combining data in the form of matrices or tables, and triangulation strategies to describe the results of analysis and research findings. Data analysis is done using NVivo 12 software. The results of the evaluation and the implementation of the nutrition self-sufficiency policy have been planned, socialized, and carried out by the main tasks and functions of related OPDs, which are carried out in an integrated manner. The stunting prevalence rate has decreased in prevalence to 9.9%. Recommendation, For the implementation of standardized activities to be made standard operating procedures (SOPs), it is necessary to strengthen operators in input and synchronize stunting data.